The importance of physical characteristics among Algerian amateur boxers - hamrouche, ahmed ridha; guerione, khaled; mhimdat, rachid (sports creativity, 2025)
Attention is one of the important psychological skills for students in sports institutes. It is the foundation for the success of the learning or training process in its various forms. Distraction or lack of focus negatively affects performance and achievement. The greater a student's ability to focus on what they are doing, the better response they will achieve. A student who lacks focus, even slightly, will negatively affect their performance and prevent them from achieving their maximum possible performance and achievement. Focus is one of the important means to raise the level of athletes and their ability to observe things accurately and clearly. An athlete can prove and develop their ability to control themselves and their surroundings and greatly increase their focus under various circumstances, especially when they can change their behavior and feelings in accordance with the situation. This works to harmonize the mind with the body. Controlling attention also helps in the process of moving from narrow to broad attention. The quality of focus plays an important role in the field of achievement. It is considered one of the important factors that affect the level of skill performance. Schleppenberger confirms that attention is a selective, organizing, and directive function of human consciousness and includes the relationship between the individual and the environment, as well as between feeling and activity.